Conceptualizing Practical Aspects of Public Library Initiatives Provides a Useful Model for Future Research - Sharun, Sara (Evidence Based Library and Information Practice, 2015)
A Review of: Sung, H. Y., Hepworth, M., & Ragsdell, G. (2013). Investigating essential elements of community engagement in public libraries: An exploratory qualitative study. Journal of Librarianship and Information Science 45(3), 206-218. doi: 10.1177/0961000612448205 Objective – To examine characteristics of a community engagement (CE) initiative in a public library in order to identify and describe essential elements of CE and develop a model for CE in public libraries. Design – Case study. Setting – A public library in a mid-sized city in England, United Kingdom. Subjects – An unspecified number of community members, library staff, and external agency staff participating in a community news program. Methods – There were 12 semi-structured interviews conducted with library staff, community members, and participants from 12 community news agencies operating under the umbrella of a larger community news organization. The authors directly observed an unknown number of undescribed program meetings and events. They also performed document analysis on unspecified government policies, media reports, and program publications to corroborate the information gathered from their interviews and observations. Main Results – The data were analyzed in an inductive manner using ATLAS qualitative data analysis software. Results are described in a qualitative manner and do not correspond directly to the individual methods used. The coding of data from interviews and observations (which are not analyzed separately) resulted in the identification of seven themes related to community engagement in libraries: belonging, commitment, communication, flexibility, genuineness, relevance, and sustainability. Conclusion – The “essential elements” model that was developed from this case study can be applied by other public libraries in their processes and practices, and can contribute to the creation of a more genuinely community-driven approach to service.